Performance of screw–shaft pile in sand: Model test and DEM simulation. (December 2018) - Chen, Yadong; Deng, An; Wang, Anting; Sun, Huasheng
Abstract: A screw–shaft pile is a bored, cast-in-situ, displacement foundation solution. This study examines the performance of axially loaded screw–shaft piles by laboratory model tests, digital image correlation, and discrete element modelling. The results suggested that the screw section carried a greater vertical load than the corresponding section of the control pile; hence, the screw–shaft pile outperformed the control pile. The screw–shaft pile achieved better performance by influencing a larger volume of sand. The sand around the screw section exhibited enlarged cone-shape shear slips and contributed to gains in the pile capacity.